On the Effects of COVID-19 Safer-At-Home Policies on Social Distancing, Car Crashes and Pollution - Abel Brodeur; Nikolai Cook; Taylor Wright (Institute of Labor Economics (IZA), 2020)
In response to COVID-19, dramatic safer-at-home policies were implemented. The understanding of their impacts on social distancing, travel and pollution is in its infancy. We pair a differences-in-differences framework and synthetic control methods with rich cellular tracking and high frequency air pollution data. We find that state and U.S. county safer-at-home policies are successful in encouraging social distance; beginning the day of the policy trips outside the home are sharply decreased while time in residence rises sharply. With less vehicle traffic, we find: a 50% reduction in vehicular collisions; an approximately 25% reduction in Particulate Matter (PM2.5) concentrations; and a reduction of the incidence of county-days with an air quality index of code yellow or above by two-thirds. We calculate that the benefits from avoided car collisions could range from 7 billion to 24 billion while the benefits from reduced pollution could range from 650 million to 13.8 billion.
Keywords: P48; Q53; Q58; 330; COVID-19; safer-at-home; lockdowns; pollution; traffic; car crashes